PAKUALAMAN HERITAGE WALK: REVITALIZING CULTURAL TOURISM THROUGH SUSTAINABILITY AND COMMUNITY EMPOWERMENT (International Conference on Economics, Business, and Management Research (ICEBMR), 2025)
Yogyakarta tourism is currently dominated by popular destinations such as Borobudur, Prambanan, Malioboro, and the Kraton, resulting in tourist overcrowding and reduced comfort. The Pakualaman historical area, with its rich cultural heritage and yet underutilized potential, provides an opportunity to diversify tourist flows. This paper explores the design of the Pakualaman Heritage Walk by integrating the concepts of Sustainable Tourism Development and Community-Based Tourism (CBT). Using a qualitative descriptive approach and case study method, the research highlights three aspects: (1) sustainable tourism pillars (environmental, socio-cultural, economic), (2) community empowerment through local participation, and (3) heritage-based product innovation. Findings indicate that the heritage walk can reduce pressure on mainstream destinations, enhance cultural awareness, empower local communities, and promote the branding of Pakualaman as a living heritage. The study contributes to the discourse on heritage-based tourism planning that is sustainable, inclusive, and culturally grounded.
Keywords: Human Resource Management; Organizational Restructuring; Qualitative Case Study; HRD Transformation